ANALISIS PERSEDIAAN BAHAN BAKU KEDELAI DENGAN MENGGUNAKAN METODE ECONOMIC ORDER QUANTITY (EOQ) PADA UD. KARYA MANDIRI SAMARINDA - Heri Surya (OBOR: Oikonomia Borneo, 2019)
This study aims to determine the optimal amount of inventory costs by comparing the inventory management of soybean raw materials with inventory management using the Economic Order Quantity (EOQ) method at UD Karya Mandiri Samarinda. In this study using an analytical tool with the Economic Order Quantity (EOQ) method to find out the optimal amount and cost of inventory, and assisted by other analytical tools, namely Safety Stock, Re Order Point, total ordering cost, total storage cost and total inventory cost. From the results of the analysis, it is known that inventory management using the Economic Order Quantity (EOQ) method is more optimal than UD inventory management. Samarinda's Independent Works. The test results state that together the EOQ method can minimize inventory costs.